Improving Student Learning Outcomes Of Class X MAN 1 Indramayu Through The Application Of Differentiated PjBL Learning Model - Hamidah, Idah; Subkhi, Nur; Nais, Jesicha; Ratnasari, Anilia (Gema Wiralodra, 2025)
The differentiated Project Based Learning model offers an interesting solution. The PJBL model itself is a model that exposes X-2 MAN 1 Indramayu students to relevant learning, which positively influences the development of student's creative thinking, allowing students to actively explore knowledge, ask questions, find problems, design, and implement projects. This study aims to improve the learning outcomes of X-2 MAN 1 Indramayu students by applying the differentiated PJBL learning model. Using a quantitative percentage method. The subjects in this study were 26 students of class X-2 MAN 1 Indramayu in the 2024/2025 academic year. Based on the study's results, the differentiated PJBL learning model was successfully applied to see student learning outcomes. As many as 55.6% of students got high learning outcomes, 30.8% of students were in the middle, and 13,6% of students were in the middle criteria. Overall, it can be concluded that the average student learning outcomes achieve high criteria in the visual learning style (45.6%), meaning that student learning outcomes are considered good after learning using the differentiated PJBL model.